Nickel Entrapped K10-Montmorillonite Composite Incorporated Al Alloy for Cathodic Protection - Archana, S.R.; Raj, S. Saalin; Mathai, Suja; Suma, M.S. (Asian Journal of Chemistry, 2018)
The galvanic performance of aluminum sacrificial anodes, which are extensively used for cathodic protection of steel structures in sea water, can be significantly improved by the presence of nickel. However the fabrication of such an alloy evenly distributed with nickel is very difficult. In the present case, Ni(0) was entrapped into montmorillonite (MMT) to prevent the agglomeration of metal nanoparticles. The resultant composite was incorporated into Al + 5 wt % Zn alloy for enhanced galvanic performance. The metallurgical characteristics of the metal-metal matrix were improved by the incorporation of nickel entrapped K10-MMT nanocomposite. Enhanced interfacial activation was achieved as evidenced from the results of impedance spectroscopic analysis. The Ni-MMT composite facilitated enhanced chloride ion adsorption from the solution of high chloride ion concentration. The developed anode possessed very high galvanic efficiency even under aggressive chloride concentration.